2008
DOI: 10.1029/2007jd009442
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing signatures of aerosol‐cloud interactions from satellite retrievals and the GISS GCM to constrain the aerosol indirect effect

Abstract: [1] Evidence of aerosol-cloud interactions is evaluated using satellite data from MODIS, CERES, and AMSR-E; reanalysis data from NCEP; and data from the NASA Goddard Institute for Space Studies climate model. We evaluate a series of model simulations: (1) Exp N, aerosol direct radiative effects; (2) Exp C, like Exp N but with aerosol effects on liquid-phase cumulus and stratus clouds; and (3) Exp CN, like Exp C but with model wind fields nudged to reanalysis data. Comparison between satellite-retrieved data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 43 publications
(61 reference statements)
8
56
1
Order By: Relevance
“…By virtue of their large coverage and high spatial and temporal resolution, satellite-borne instruments have become a promising observational tool in studying ACIs. Previous studies using a large amount of satellite data and/or multiple satellite instruments have shown that aerosol particles can affect cloud properties significantly (Krüger and Grassl, 2002;Menon et al, 2008;Sporre et al, 2014;Rosenfeld et al, 2014;Saponaro et al, 2017). Satellite measurements suggest that the CDR tends to decrease with increasing aerosol loading, which is consistent with Twomey's theory (Matheson et al, 2005;Meskhidze and Nenes, 2010;Koren et al, 2005).…”
Section: Introductionsupporting
confidence: 76%
“…By virtue of their large coverage and high spatial and temporal resolution, satellite-borne instruments have become a promising observational tool in studying ACIs. Previous studies using a large amount of satellite data and/or multiple satellite instruments have shown that aerosol particles can affect cloud properties significantly (Krüger and Grassl, 2002;Menon et al, 2008;Sporre et al, 2014;Rosenfeld et al, 2014;Saponaro et al, 2017). Satellite measurements suggest that the CDR tends to decrease with increasing aerosol loading, which is consistent with Twomey's theory (Matheson et al, 2005;Meskhidze and Nenes, 2010;Koren et al, 2005).…”
Section: Introductionsupporting
confidence: 76%
“…Aerosol particles can influence the earth's climate both directly by scattering and absorption of incoming solar radiation and terrestrial outgoing radiation, and indirectly by affecting cloud radiative properties through their role as cloud condensation nuclei (CCN) and ice nuclei (IN) (Twomey, 1974(Twomey, , 1991Charlson et al, 1992;Yu, 2000;Yu et al, 2000Yu et al, , 2001aYu et al, , b, 2003Yu and Zhang, 2011;Lohmann and Feichter, 2005;Menon et al, 2002Menon et al, , 2008IPCC, 2007;DeFelice et al, 1997;Chapman et al, 2009;Gustafson et al, 2007;Zhang et al, 2010aZhang et al, , b, 2012Tao et al, 2012;Hansen et al, 1997;Haywood and Boucher, 2000;Ramanathan et al, 2001;Rosenfeld et al, 2008;Saxena and Yu, 1998;Saxena et al, 1997;F. Yu et al, 2012a, b;Saide et al, 2012;Yang et al, 2011;Liu et al, 2011;McKeen et al, 2007;Yu et al, 2004Yu et al, , 2007bYu et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous completed studies attempt to understand aerosol effects on liquid phase clouds (e.g. Jiang et al, 2006;Lu and Seinfeld, 2005;Menon et al, 2008), less attention has been given to similar interactions in mixed-phase clouds (e.g. Lohmann and Diehl, 2006).…”
Section: Introductionmentioning
confidence: 99%